Sentinel Lymph-Node Biopsy in Early-Stage Cervical Cancer: The 4-Year Follow-Up Results of the Senticol 2 Trial - Favre, Guillaume; Guani, Benedetta; Balaya, Vincent; Magaud, Laurent; Lecuru, Fabrice; Mathevet, Patrice (Frontiers in Oncology, 2021)
Introduction Senticol 2 is a randomized multicenter trial in the treatment of early-stage cervical cancer patients. The aim of the Senticol 2 study was to compare the effect of sentinel-lymph-node biopsy (SLNB) to that of SLNB + pelvic lymphadenectomy (PLND), and to determine the postoperative lymphatic morbidity in the two groups. Here, we report a secondary objective of this study: the follow up. Material and Methods In the Senticol 2 trial, patients underwent a laparoscopy with a sentinel-node-detection procedure and were randomized into two groups, namely: Group A, in which participants received SLNB, and Group B, in which participants received SLNB + PLND. Patients with an intra-operative macroscopically suspicious lymph node, were given a frozen-section evaluation and were randomized only if the results were negative. All of the patients received follow up with a clinical examination at 1, 3, and 6 months after surgery, and then every 3–4 months after that. The median follow up was 51 months (4 years and 3 months). Results Disease-free survival after 4 years for the SLNB group and the SLNB + PLND group were 89.51% and 93.1% (p = 0.53), respectively. The only statistical factor associated with recurrence in the univariate analysis was the adjuvant radiotherapy. No other factors, including the age of the patients, histological type, tumor size, lymph vascular space invasion (LVSI), and positive nodal status, were significant in the univariate or multivariate analyses. The overall survival rates after 4 years in the SLNB and SLNB + PLND groups were 95.2% and 96% (p = 0.97), with five and four deaths, respectively. The univariate and multivariate analyses did not find any prognostic factors. Conclusions This randomized study confirmed the results of the Senticol 1 study and supports the sentinel lymph node (SLN) technique as a safe technique for use in patients with early-stage cervical cancer treated with SLNB only. Disease-free survival after 4 years was similar in patients treated with SLN biopsy and patients who underwent a lymphadenectomy.